2019
DOI: 10.1093/rpd/ncy283
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Eye Lens Dose Estimated Using Whole-Body Dosemeter in Interventional Cardiology and Radiology: A Monte Carlo Study

Abstract: Medical personnel performing interventional procedures in cardiology and radiology is considered to be a professional group exposed to high doses of ionizing radiation. Reduction of the eye lens dose limit made its assessment in the interventional procedures one of the most challenging topics. The objective of this work is to assess eye lens doses based on the whole-body doses using methods of computational dosimetry. Assessment included different C-arm orientations (PA, LAO and RAO), tube voltages (80 –110 kV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Scrub nurses are generally positioned further away from the most significant source of x-ray scatter, which suppositionally reduces their level of exposure compared to the doctor. Still, it has been reported that nursing staff may be exposed to higher levels of radiation than the doctor due to the shelter provided by the CMLS 28 30 , and this may be a contributing factor in the increased dose to scrub nurses. The presence of the X-ray detector has also been identified as providing an incidental protective barrier to doctors’ heads by absorbing X-ray photons, depending on the position of the doctor 18 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Scrub nurses are generally positioned further away from the most significant source of x-ray scatter, which suppositionally reduces their level of exposure compared to the doctor. Still, it has been reported that nursing staff may be exposed to higher levels of radiation than the doctor due to the shelter provided by the CMLS 28 30 , and this may be a contributing factor in the increased dose to scrub nurses. The presence of the X-ray detector has also been identified as providing an incidental protective barrier to doctors’ heads by absorbing X-ray photons, depending on the position of the doctor 18 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Safety measures to prevent radiation exposure are important due to the risk of radiation-induced injuries, such as skin damage in patients and cataracts in medical staff [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Therefore, increasing attention is being paid to radiation safety and protection for patients and medical staff, particularly related to IVR [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Farah et al [18] performed phantom simulations finding wide dispersion in the values of eye/chest ratio, depending on the type of projections, the location of the chest dosimeter (left, right, middle) and whether the x-ray system is monotube or biplane, and conclude that for interventional cardiology studies, a factor of 0.7 with an spread of 40% can be used to estimate the eye lens dose from chest readings (for retrospective dose assessment in the ELDO project). A Monte Carlo simulation performed by Bozovic et al [17] obtained conversion factors between chest and eyes of 0.98 and 1.66 depending on the role/position of the interventionalist, i.e. 1st operator, 2nd operator or 3rd operator.…”
Section: Dosimeter On the Glasses Versus Dosimeter On The Chest Over ...mentioning
confidence: 99%
“…Using dosimeters on the thyroid collar or on the chest over the apron are more practical options to estimate eye doses and in some situations makes unnecessary a dosimeter close to the eye. There are studies that examine the relationship between the dose measured at the neck or on the chest over the apron with the dose received at eye level by means of Monte Carlo simulations [17], phantom simulations [18][19][20] and measurements in clinical procedures [21][22][23][24][25][26][27], some of them suggesting that accurate correction factors could be operator dependant.…”
Section: Introductionmentioning
confidence: 99%